Modelos de negócio para empresas de distribuição de energia elétrica criar, entregar e capturar valor da geração distribuída - Balestra, Grégori da Cruz (2022)
The significant growth of distributed generation has been affecting the economic-financial balance of electricity distribution companies, creating the need to develop business models suited to the new context. This work presents a method to systematically identify, characterize and classify the business models used by the companies that were mentioned before, to create, deliver and capture value in the new environment created by GD. An analysis is also made of how and which business models can be applied considering the current Brazilian legislation, highlighting the barriers that must be faced. To identify the business models, a survey was carried out based on secondary data obtained from the literature review and search on distributors' websites. To systematically categorize these models, three main elements were used: revenue flow, customer segments and value propositions. After categorization, each model was characterized using a systemic map in which the main actors involved and how they relate to each other are pointed out. Finally, the use of each category was evaluated considering the Brazilian regulatory environment. The application of the proposed taxonomy allowed the business models to be grouped into seven categories, whose characteristics are presented in relation to international experience. The results obtained allow us to conclude that distribution companies need to innovate in their business models to adapt to the new context created by DG. Regarding Brazilian matters, it is necessary that regulatory changes occur that allow distributors to be remunerated for sources of revenue that exceed the traditional energy supply service.